Money demand stability: A case study of Nigeria - Saten Kumar; Don J. Webber; Scott Fargher (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2011)
This paper presents an empirical investigation into the level and stability of money demand (M1) in Nigeria between 1960 and 2008. In addition to estimating the canonical specification, alternative models are presented that include additional variables to proxy for the cost of holding money. Results suggest that the canonical specification is well-determined, the money demand relationship went through a regime shift in 1986 which slightly improved the scale economies of money demand, and money demand is stable. These findings question the appropriateness of the Central Bank of Nigeria's new monetary policy framework in which short-term interest rates play a crucial role and imply that Nigeria could effectively use the supply of money as an instrument of monetary policy.
Keywords: E21; C22; 330; Money demand; Structural breaks; Cointegration; Monetary policy